Three‐dimensional physics‐based registration of pelvic system using 2D dynamic magnetic resonance imaging slices. (15th April 2020) - Courtecuisse, H.; Jiang, Z.; Mayeur, O.; Witz, J. F.; Lecomte‐Grosbras, P.; Cosson, M.; Brieu, M.; Cotin, S.
Abstract: This paper introduces a method for dynamic 3D registration of female pelvic organs using 2D dynamic magnetic‐resonance images (MRIs). The aim is to provide a better knowledge and understanding of pathologies such as prolapsus or abnormal mobility of tissues. 2D dynamic MRI sequences are commonly used in nowadays clinical routines in order to evaluate the dynamic of organs, but due to the limited view, subjectivity related to human perception cannot be avoided in the diagnoses. A novel method for 2D/3D registration is proposed combining 3D finite element models with a priori knowledge of boundary conditions, in order to provide a 3D extrapolation of the dynamic of the organs observed in a single 2D MRI slice. The method is applied to the four main structures of the female pelvic floor (bladder, vagina, uterus and rectum), providing a full 3D visualisation of the organs' displacements. The methodology is evaluated with two patient‐specific data sets of volunteers presenting no pelvic pathology, and a sensitivity study is performed using synthetic data. The resulting simulations provide an estimation of the dynamic 3D shape of the organs facilitating diagnosis compared with 2D sequences. Moreover, the method follows a protocol compatible with current clinical constraints presenting this way potential short term medical applications.